Inhibition of peripheral chemoreceptors improves ventilatory efficiency during exercise in heart failure with preserved ejection fraction − a role of tonic activity and acute reflex response - Kulej-Lyko, Katarzyna; Niewinski, Piotr; Tubek, Stanislaw; Krawczyk, Magdalena; Kosmala, Wojciech; Ponikowski, Piotr (Frontiers in Physiology, 2022)
Peripheral chemoreceptors (PChRs) play a significant role in maintaining adequate oxygenation in the bloodstream. PChRs functionality comprises two components: tonic activity (PChT) which regulates ventilation during normoxia and acute reflex response (peripheral chemosensitivity, PChS), which increases ventilation following a specific stimulus. There is a clear link between augmented PChS and exercise intolerance in patients with heart failure with reduced ejection fraction. It has been also shown that inhibition of PChRs leads to the improvement in exercise capacity. However, it has not been established yet: 1) whether similar mechanisms take part in heart failure with preserved ejection fraction (HFpEF) and 2) which component of PChRs functionality (PChT vs. PChS) is responsible for the benefit seen after the acute experimental blockade. To answer those questions we enrolled 12 stable patients with HFpEF. All participants underwent an assessment of PChT (attenuation of minute ventilation in response to low-dose dopamine infusion), PChS (enhancement of minute ventilation in response to hypoxia) and a symptom-limited cardiopulmonary exercise test on cycle ergometer. All tests were placebo-controlled, double-blinded and performed in a randomized order. Under resting conditions and at normoxia dopamine attenuated minute ventilation and systemic vascular resistance (p=0.03 for both). These changes were not seen with placebo. Dopamine also decreased ventilatory and mean arterial pressure responses to hypoxia (p<0.05 for both). Inhibition of PChRs led to a decrease in V˙E/V˙CO2 comparing to placebo (36±3.6 vs. 34.3±3.7, p=0.04), with no effect on peak oxygen consumption. We found a significant relationship between PChT and the relative decrement of V˙E/V˙CO2 on dopamine comparing to placebo (R=0.76, p=0.005). There was a trend for correlation between PChS (on placebo) and V˙E/V˙CO2 during placebo infusion (R=0.56, p=0.059), but the relative improvement in V˙E/V˙CO2 was not related to the change in PChS (dopamine vs. placebo). We did not find a significant relationship between PChT and PChS. In conclusion, inhibition of PChRs in HFpEF population improves ventilatory efficiency during exercise. Increased PChS is associated with worse (higher) V˙E/V˙CO2, whereas PChT predicts an improvement in V˙E/V˙CO2 after PChRs inhibition. This results may be meaningful for patient selection in further clinical trials involving PChRs modulation.